Digital Skill Advantage as a Mediating Mechanism between Career Efficacy, Digital Mindset, and Career Readiness among Generation Z Students - Cici Dea Permata Exsti; Bella Mei Mulya Wati; Aulia Hakim (Program Studi Manajemen Pendidikan, 2026)
The primary objective of this study is to explore how career efficacy and digital mindset shape career readiness, with digital skill advantage serving as a mediating variable, among Generation Z students in Indonesia. A quantitative research design with a cross-sectional framework was employed in this study. Primary data were gathered via an online survey instrument distributed to 100 active undergraduate students in Central Java through purposive sampling procedures. The resulting data were then subjected to analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 as the analytical tool. The results demonstrate that both career efficacy and digital mindset exert positive and statistically significant impacts on career readiness and digital skill advantage alike. Moreover, digital skill advantage plays a meaningful mediating role in the pathways linking career efficacy to career readiness and digital mindset to career readiness. These outcomes underscore the pivotal function of superior digital competencies in bolstering student career preparedness within the current digital landscape. This research advances Social Cognitive Career Theory (SCCT) by establishing digital skill advantage as a mediating construct that connects individual internal attributes to career readiness outcomes.